Revisiting Abdurrahman Wahid’s Concept of Pluralism: Implications for Inclusive Islamic Education in Indonesia - Fahreza Aidhil Maddini; Nur Aulia Fitri; Annisa Hasli; Nur Fadila; Nur Hidayah (Journal of Indonesian Islamic Studies, 2024)
Indonesia’s religious and cultural diversity presents both opportunities and challenges for Islamic education in fostering social cohesion, tolerance, and mutual respect. In recent years, increasing concerns regarding religious intolerance, identity-based polarization, and exclusivist interpretations of religion have highlighted the need for inclusive educational approaches grounded in Islamic values. This study aims to revisit Abdurrahman Wahid’s concept of pluralism and examine its implications for inclusive Islamic education in Indonesia. Employing a qualitative library research design, the study utilizes philosophical and historical approaches to analyze Abdurrahman Wahid’s writings and relevant scholarly literature. The findings reveal that Gus Dur’s concept of pluralism is constructed upon three major pillars: Islamic universalism, Islamic cosmopolitanism, and the indigenization of Islam. These concepts collectively promote respect for human dignity, openness to intercultural dialogue, and the harmonious integration of Islamic teachings with local cultural traditions. The study further demonstrates that Gus Dur’s pluralistic thought provides a strong conceptual foundation for inclusive Islamic education by emphasizing tolerance, mutual understanding, social justice, and democratic values while maintaining commitment to Islamic principles. Unlike previous studies that primarily focus on the political or theological dimensions of Gus Dur’s thought, this article highlights its educational significance in addressing contemporary challenges related to diversity and social cohesion. The study concludes that Abdurrahman Wahid’s pluralistic vision remains highly relevant for strengthening inclusive, moderate, and socially responsive Islamic education in contemporary Indonesia.